Complex behavior of prey-predator system exhibiting group defense: A mathematical modeling study. (July 2017) - Raw, S.N.; Mishra, P.; Kumar, R.; Thakur, S.
Highlights: The manuscript focuses the effect of group defense ability in population. A three species prey-predator model with Monod-Haldane functional response is considered. We have investigated the dynamical behavior of the model system to explore the possibility of the chaos through the numerical simulation. The effect of immigration is studied within top predator population. Abstract: Defense mechanisms are very important to all animal life. Predators in every biome must eat to survive. With predators being top on the food chain and always on the lookout for a meal, prey must constantly avoid being eaten. In this paper, we have proposed and analyzed a tri-trophic predator–prey model of one prey and two predator exhibiting group defense mechanism. We have assumed Monod-Haldane functional response for interaction between species due to group defense ability of prey and middle predator. We have performed Kolmogorov and Hopf bifurcation analysis for the model system. Linear and global stability of the model system have been analyzed. Lyapunov exponents are computed numerically and 2D scan for different parameters of the model have performed to characterize the complex behavior of the model system. The numerical simulations shows the chaotic and periodic oscillations of the model system for certain range of parameter. We have drawn bifurcation diagrams for different parameter values which shows the complex dynamical behavior of model system. This work is an attempt to study the effect of group defense mechanism of prey in predator population and effect of immigration within top predator population is investigated. It is also observed that in the presence of group defense, the model system stabilizes after adding a small amount of constant immigration within top predator population.